Filtenna Designed with Patterned Ground Structure for Microwave Imaging Applications - Dayang Azra, Awang Mat; Dyg Norkhairunnisa, Abang Zaidel; Kismet, Hong Ping
The rapid development of microwave communication systems correlates to the desire for low-cost, small, and highly efficient systems. This is when the concept of integrating the filter and antenna into a single component was established. This concept was proposed because the impedance mismatch between the proposed antenna and filter separately causes interference, increases insertion loss, and consequently affects the overall performance of the circuit.